Tandem Azolation/Aromatization of Tetrahydronaphthalenes with Hydrogen Evolution via Organophotoredox/Cobalt Dual Catalysis - Huang, Cheng; Tang, Sheng; Wang, Chen-Lu; Kang, Chen; Wang, Ying; Jing, Yaru; Ye, Zhong-Ming; Wei, Zhenhong; Cai, Hu (Organic letters, 2025)
Reported herein is a photoredox/cobaloxime dual-catalytic approach to execute tandem dehydrogenative azolation and aromatization of tetrahydronaphthalene for rapid construction of N-(β-naphthyl)azole architectures. This protocol highlights noble metal-free and external oxidants-free conditions, step- and atom-economy, and site-selectivity. A preliminary mechanistic study has uncovered that the transformation undergoes a N-centered radical mediated C–H/N–H cross-coupling followed by dehydrogenative aromatization of saturated naphthyl surrogates under visible light irradiation, and DFT calculations elucidate the site-selectivity.